A Descriptive Study of Teachers’ Questioning Strategies in English Classroom Interaction at SMAN 2 Taruna Bhayangkara in the Academic Year 2019/2020 - Ary Yashinta Devi; Wulan Wangi; Abdul Halim (LUNAR, 2020)
Questioning strategies are the important method for teachers to ask the students by giving the question. The goal of this research was to identify out the type and the level of questioning strategies that used by the English techers in English classroom interaction at SMAN 2 Taruna Bhayangkara in the academic year 2019/2020. This research used descriptive qualitative research design. There were 6 English teachers as the respondents. It determined by using purposive sampling. To collect the data, it taken by using questionnaire and interview. Likert scale was the tool to analyze the data from quistionnaire. To determine the data analysis, it related to eight indicators namely wait time, probing question, balance, participation, prhasing, sequencing, adaptation, and student question. From the data analysis, it offered that questioning strategies always use by the teachers in English classroom interaction. The percentage of wait time was 80.56%, probing question 79.17%, balance 61%, participation 76.39%, phrasing 87.5%, sequencing 80.56%, adaptation 68.06%, student question 73.61%. In addition, the most performed type of questioning strategies was phrasing (87.5%) and based on the Bloom’s Taxonomy, teachers used of model questions in understanding level which has indicated in lower level question. Thus, the English teachers should develop questions in higher level to stimulate students higher order thinking skill.